1998
DOI: 10.1209/epl/i1998-00303-0
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effect on m * in high- T c materials due to the breakdown of Migdal's theorem

Abstract: PACS. 71.38+i -Polarons and electron-phonon interactions. PACS. 74.25Kc -Phonons. PACS. 71.18+y -Fermi surface: calculations and measurements; effective mass, g factor.Abstract. -We show that the inclusion of effects beyond Migdal's limit in the electron-phonon interaction naturally leads to an isotope effect for the effective mass m * of the charge carriers even much before reaching the polaron limit. This is the situation already considered in our approach to nonadiabatic superconductivity [7]. Such a result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 23 publications
2
55
0
Order By: Relevance
“…The effective mass m * represents therefore a clear example of a quantity for which a well established property in the ME regime (α m * = 0) is drastically modified in the nonadiabatic one (α m * = 0). So far, strong evidences for isotopedependent m * have been reported for YBa 2 Cu 3 O 6+x and La 2−x Sr x CuO 4 [13] and theoretical calculations have shown that already the inclusion of the first nonadiabatic vertex correction to the ME limit provides values of α m * with sign and order of magnitude in agreement with those estimated by the experiments [12].…”
supporting
confidence: 74%
“…The effective mass m * represents therefore a clear example of a quantity for which a well established property in the ME regime (α m * = 0) is drastically modified in the nonadiabatic one (α m * = 0). So far, strong evidences for isotopedependent m * have been reported for YBa 2 Cu 3 O 6+x and La 2−x Sr x CuO 4 [13] and theoretical calculations have shown that already the inclusion of the first nonadiabatic vertex correction to the ME limit provides values of α m * with sign and order of magnitude in agreement with those estimated by the experiments [12].…”
supporting
confidence: 74%
“…Cappelluti, C. Grimaldi, L. Pietronero, and S. Strässler [16][17][18][19] give correct estimations of the order of magnitude and sign of the nonadiabatic corrections to the self-energy. The analytical results were compared with numerical calculations.…”
Section: Discussionmentioning
confidence: 97%
“…An approximation for q → 0 was used 24 and then q c = Q c · 2p F was set to q c = 2p F giving the following result 19 for Z:…”
mentioning
confidence: 99%
“…The detection of isotope effects on various quantities receives a crucial importance in the nonadiabatic framework since it directly probes the nonadiabatic nature of el-ph interaction. In particular it has been shown that nonadiabatic effects give rise to a finite isotope effect on quantities which in conventional ME theory are expected to not show it, for instance the effective electron mass m * [29] and the spin susceptibility χ [30]. The actual discovery of an anomalous isotope effects on these or other quantities represents therefore a precise prediction of the nonadiabatic theory which could be experimentally checked.…”
mentioning
confidence: 99%